Green composites : polymer composites and the environment - Baillie, Caroline (CRC Press ; Woodhead Pub., 2004)
There is an increasing movement of scientists and engineers dedicated to minimising the environmental impact of polymer composite production. Life-cycle assessment is of paramount importance at every stage of a product's life, from initial synthesis through to final disposal and a sustainable society needs environmentally safe materials and processing methods. With an internationally recognised team of authors, Green composites examines polymer composite production and explains how environmental footprints can be diminished at every stage of the life-cycle. This book is an essential guide for agricultural crop producers, governmental agricultural departments, automotive companies, composite producers and material scientists all dedicated to the promotion and practice of eco-friendly materials and production methods.